The Influence of Discipline, Motivation, and Teacher Performance Satisfaction on Teacher Performance at Junior High School - Oktavia, Aisyah; Fadhli, Muhammad (research, training and philanthropy institution Natural Aceh, 2025)
This study aims to analyze the influence of work discipline, work motivation, and job satisfaction on teacher performance at SMP IT Al Maksum Sunggal. This study's background is based on some teachers' weak performance, such as inconsistency in preparing learning tools, low variation in teaching methods, and varying levels of discipline and job satisfaction. This study uses a quantitative approach with the Partial Least square-structural Equation Modeling (PLS-SEM) analysis method through the SmartPLS 3.0 application. The respondents were 30 teachers, which was determined through total sampling techniques. The study showed that the three independent variables simultaneously influenced teacher performance with an R² value of 0.441. Partially, work discipline has a positive and significant effect on teacher performance (path coefficient = 0.505), but several indicators, such as DG2 and DG5, have low loading values ​​and need to be evaluated. Conversely, work motivation negatively affects teacher performance (coefficient = -0.159), which indicates the possibility of conceptual problems in measuring indicators. Job satisfaction is the most consistent and significant variable influencing teacher performance (coefficient = 0.350), with strong reliability and convergent validity support. Thus, strengthening teacher discipline and job satisfaction must be the focus of human resource development in schools. In contrast, the motivation aspect needs to be reviewed conceptually and technically to maximize its contribution to improving teacher performance.